Few differences in hot and cold executive functions in children and adolescents with combined and inattentive subtypes of ADHD - Skogli, Erik Winther; Egeland, Jens; Andersen, Per Normann; Hovik, Kjell Tore; Øie, Merete (Child neuropsychology, 2014)
The aim of the study was to compare executive processes with pronounced (hot) and less pronounced (cold) emotional salience in medication naïve children and adolescents with ADHD-combined (ADHD-C) and ADHD-inattentive (ADHD-I) subtypes. Thirty-six subjects with ADHD-C, 44 with ADHD-I, and 50 healthy controls between 8 and 17 years were assessed with laboratory tests and inventory-based scales assessing hot and cold executive functions (EF) (controlled attention, working memory, planning, cognitive flexibility, verbal fluency, hot decision making) and the Behavior Rating Inventory of Executive Function (BRIEF). The ADHD-C group displayed significantly more impairment compared to the ADHD-I group on the cold BRIEF Inhibition and Monitor scales. There were no significant differences between ADHD subtypes on cold and hot laboratory tests. The hot decision-making task did not correlate with the other cold or hot EF measures. Overall, few EF measures were shown to differentiate between ADHD subtypes nor were there any relationships between the hot decision-making task and the other EF measures, which seems to indicate separate developmental trajectories.